The Role of Notaries in Agreements Made by Individual Companies with Other Parties - Mulia, Fina Adinda; Hafidz, Jawade (Jurnal Konstatering, 2024)
Agreements made between individual companies and other parties require the role of a notary so that the parties are protected from legal problems in the future. This study aims to determine the role of a notary in agreements made by individual companies with other parties and to determine the obstacles faced by notaries in agreements made by individual companies with other parties. The research approach method used in this thesis is an empirical legal research method, The specifications of this research are descriptive analytical, The type of data used in this study uses primary data which includes: the 1945 Constitution, the Civil Code, Law No. 40 of 2007 concerning Limited Liability Companies, Law No. 11 of 2020 concerning Job Creation, Government Regulation No. 8 of 2021 concerning the Authorized Capital of Companies and Registration of the Establishment, Amendments, and Dissolution of Companies That Meet the Criteria for Micro and Small Businesses. As well as secondary data containing books and other supporting documents. Collection of research data using interview techniques, observation and literature studies. The data analysis method uses qualitative data analysis techniques. The results of the study show that: First, in an agreement between a sole proprietorship and another party, the role of a notary cannot be ignored. A notary has roles such as: Providing legal advice and considerations, Ensuring that the agreement document is correct and complete, Formulating the will of the parties, Issuing a copy of the agreement deed to all parties involved, Safely storing the authentic agreement deed that has been made. Second, the constraints of a notary in an agreement made by a sole proprietorship with another party: Lack of understanding of the parties about the law, Incomplete documents, Lack of information from the parties, Disagreement of the parties.Keywords: Agreement; Notary; Proprietorship; Sole.